Adjunctive Treatment With Eslicarbazepine Acetate for Adults and Children With Focal-Onset Epilepsy: A Meta-Analysis - Fei, Yanqing; Shi, Ruting; Song, Zhi (Frontiers in Neurology, 2022)
Background The efficacy and tolerability of eslicarbazepine acetate (ESL) in adults and children with focal-onset epilepsy (FOE) according to the dose remain to be validated. A meta-analysis based on randomized controlled trials (RCTs) was therefore conducted as a summary. Methods Relevant RCTs were collected by systematic searching the electronic databases of PubMed, Cochrane's Library, Embase, Wanfang and CNKI from inception to May 16, 2022. The random-effect model was adopted to pool the results by incorporating the possible heterogeneity. Efficacy outcomes including responsive rate and effective rate, defined as cases with 50 and ≥75% reduction in seizure frequency compared to baseline, were determined, respectively. Incidence of severe adverse events (AE) leading to drug discontinuation was also evaluated. Results Ten studies including 2,565 people with epilepsy contributed to the meta-analysis. For adults, ESL 400 mg/d did not improve the response rate or the effective rate; ESL 800 mg/d was associated with improved response rate (odds ratio [OR] 2.16, 95% confidence interval [CI]: 1.65–2.83, p < 0.001) and effective rate (OR 2.16, 95% CI: 1.41–3.30, p < 0.001) without significantly increased severe AE (OR 1.58, 95% CI: 0.90–2.78, p = 0.11); ESL 1,200 mg/d improved response rate (OR 2.49, p < 0.001) and effective rate (OR 3.09, p = 0.04), but significantly increased severe AE (OR 3.72, p < 0.001). For children, ESL also did not significantly improve the response rate (OR 1.76, p = 0.22) or the effective rate (OR 2.17, p = 0.13). Conclusion ESL 800 mg/d is effective and well-tolerated as adjuvants for adults with FOE. Efficacy of ESL in children with FOE should be further evaluated.